Prevalensi Kejadian Miopia pada Mahasiswa Universitas Ma Chung Malang - Hendra Yuda; Joko Irawan; Kukuh Mujiono (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
The prevalence of myopia is increasing, especially among students, along with the increasing use of gadgets. This study aims to measure the prevalence of myopia and identify the relationship between the duration of gadget use and the incidence of myopia among students of Ma Chung University Malang in July 2023. This study design uses a quantitative approach with a cross-sectional method, involving 125 students aged 17–24 years who were selected using convenience sampling techniques. The research instruments were questionnaires and direct eye examinations. Data analysis used a simple linear regression test to see the relationship between independent and dependent variables. The results showed that 96.8% of respondents used gadgets for more than 2 hours per day and 58.4% of them experienced symptoms of myopia. Factors such as visual habits and outdoor activities moderate the relationship between the duration of gadget use and the incidence of myopia. This study confirms that unhealthy gadget usage habits increase the risk of myopia. Education is needed regarding good visual habits and increased activity.